1979
DOI: 10.1212/wnl.29.6.809
|View full text |Cite
|
Sign up to set email alerts
|

Brain aluminum in aging and Alzheimer disease

Abstract: Aluminum was assayed by atomic absorption spectroscopy in 274 brain samples, and assayed in neurons isolated in bulk from the frontal cortex of patients with Alzheimer dementia and from age-matched patients with no neurologic disease. Brain aluminum concentration increased with age, from late middle age to old age. There were no statistically significant differences in brain aluminum concentration between the 10 patients with Alzheimer disease (mean, 2.7 microgram per gram dry weight of tissue; mean age, 81 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
92
0
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(100 citation statements)
references
References 0 publications
5
92
0
2
Order By: Relevance
“…The controversy concerning levels of aluminum in AD brain is complicated by a lack of consensus concerning levels of aluminum in normal brain which are reported to vary by as much as 10-fold [24,25]. In the present work, cell lines were exposed to Fig.…”
Section: Discussionmentioning
confidence: 92%
“…The controversy concerning levels of aluminum in AD brain is complicated by a lack of consensus concerning levels of aluminum in normal brain which are reported to vary by as much as 10-fold [24,25]. In the present work, cell lines were exposed to Fig.…”
Section: Discussionmentioning
confidence: 92%
“…The third possibility may be that the acidic domain of APP binds to many metal ions and may form a bulky structure (Hesse et al, 1994) that may cause the translocational arrest. Many studies have implicated metal ions, including zinc, copper, iron, and aluminum, in the pathogenesis of AD (McDermott et al, 1979;Lovell et al, 1998;Zatta et al, 2003). Furthermore, some studies have also shown that the cellular concentrations of these metal ions were increased in AD brain (Basun et al, 1991;Loeffler et al, 1996;Jagannatha Rao et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Aluminum (Al) has been suggested to accelerate or play a causal role in the pathogenesis of AD. The metal is found in the brain of patients with this disorder [10, 39,541. However, other studies have been unable to confirm these findings [5,23,31 ]. [2,32,36,42].…”
Section: Introductionmentioning
confidence: 89%